(untitled) (MAUSAM, 1997)
In this paper, three numerical models of typhoon surge are discussed briefly. The first one is called Five-basin Model (FbM). The second one is called SLOSH (Sea, Lake and Overland Surges from Hurricanes), 5 SLOSH-type basins covering the entire China coastlines were developed in a joint project between authors and Jelesnianski et al. (1992) of U.S.A. The two models have been used in real-time forecasting of typhoon surge. The third one is a new developing model in which inundation using the scheme originated by Flather and Heaps (1975) and astronomical used was included. A multiple nested grid system was developed.